2015
DOI: 10.1007/s13105-015-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a reverses the inhibitory effect of hyperoxia on transdifferentiation of alveolar epithelial type II cells to type I cells

Abstract: Transdifferentiation of alveolar epithelial type II cells (AECIIs) to type I cells (AECIs) is critical for reestablishment and maintenance of an intact alveolar epithelium. However, this process is frequently destroyed by hyperoxia treatment, which is commonly used in respiratory distress syndrome therapy in preterm infants. Wnt5a is considered to participate in this physiopathologic process, but the clear mechanisms still need to be further investigated. In this study, preterm rats and primary rat AECIIs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…AECII can decrease surface tension to prevent atelectasis and absorb fluid to prevent pulmonary edema. AECII help maintain normal air exchange function of the lung, and possess stem cell function in lung development and damage repair [5,6]. Because the biological characters of AECII are highly dependent on lung microenvironment, AECII would lose specific characteristics and differentiate into AECI after in vitro culture [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AECII can decrease surface tension to prevent atelectasis and absorb fluid to prevent pulmonary edema. AECII help maintain normal air exchange function of the lung, and possess stem cell function in lung development and damage repair [5,6]. Because the biological characters of AECII are highly dependent on lung microenvironment, AECII would lose specific characteristics and differentiate into AECI after in vitro culture [22].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal inflammatory response to cigarette smoke in the lung promotes COPD development [4]. Alveolar type II epithelial cells (AECII) play important role in the maintenance of normal lung structure and help the repair and recovery of the lung after biological and physical lung damages [5,6]. Cigarette smoking has been shown to cause the apoptosis of AECII [7].…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to hyperoxia, type I cells are more susceptible to injury, and type II cells appear to increasingly proliferate and transdifferentiate into type I cells, which are resistant to oxidative damage ( 15 ). However, previous studies confirmed that hyperoxia inhibits activation of type II cells ( 16 , 17 ). A number of studies on the pathological foundation of BPD have focused on type II cell injury, with respect to proliferation, apoptosis and transdifferentiation into type I cells or mesenchymal cells (EMT).…”
Section: Discussionmentioning
confidence: 91%
“…TGF-β1, produced by AECs, is secreted during the transdifferentiation of AEC IIs to AEC Is, and the autocrine production of TGF-β1 has been shown to promote the transdifferentiation of primary rat AEC IIs to AEC Is in vitro (11,12). An autocrine loop of TGF-β1 in mammary epithelium of pregnant mice has been shown to aid the differentiation process (29).…”
Section: Discussionmentioning
confidence: 99%
“…secretory, synthetic and remodeling reservoirs for the lung epithelium to host defense (9). The AEC IIs are the progenitors of AEC Is, and the progenitor function of AEC IIs may be activated when the lung epithelium encounters a variety of stimulators, including acute lung injury or bacteria, among others, to defend the alveolus from injury (10,11). However, whether the tumor cells metastasizing to the lung are able to stimulate AEC II transdifferentiation has not been examined in detail.…”
Section: Transdifferentiation Of Type II Alveolar Epithelial Cells Inmentioning
confidence: 99%